Synthesis and Antimicrobial Evaluation of 2-Aminobenzophenone Linked 1,4-Dihydropyridine Derivatives - Li, Pengying; Sahore, Ketki; Liu, Jianjun; K. Singh, Rajesh (Asian Journal of Chemistry, 2014)
A series of novel aminobenzophenone linked 1,4-dihydropyridines (1,4-DHPs) hybrids were synthesized by incorporating aminobenzophenone moiety on 1,4-dihydropyridines scaffold (5a-f) and characterized by IR, 1H NMR and CHN elemental analysis. The synthesized compounds were tested for their in vitro antibacterial activity against the Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. Among all the synthesized compounds, compounds 5b, 5c and 5e have shown the maximum activity in their group whereas compounds 5a, 5d, 5f have shown the minimum activity.